2020
DOI: 10.1016/j.virol.2020.01.004
|View full text |Cite
|
Sign up to set email alerts
|

SPINT2 inhibits proteases involved in activation of both influenza viruses and metapneumoviruses

Abstract: A B S T R A C TViruses possessing class I fusion proteins require proteolytic activation by host cell proteases to mediate fusion with the host cell membrane. The mammalian SPINT2 gene encodes a protease inhibitor that targets trypsin-like serine proteases. Here we show the protease inhibitor, SPINT2, restricts cleavage-activation efficiently for a range of influenza viruses and for human metapneumovirus (HMPV). SPINT2 treatment resulted in the cleavage and fusion inhibition of full-length influenza A/CA/04/09… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…Further, full inhibition was observed when the camostat mesylate was coupled with Cathepsin B/L inhibitor E-64d, indicating alternate protein priming by endosomal cysteine proteases Cathepsin B/L (Hoffmann et al, 2020). These results were in concert with another study where SPINT2 geneencoded protease inhibitor targeted TMPRSS2 and led to the restriction of cleavage-activation and viral growth for a range of influenza viruses (Straus et al, 2020). Furthermore, the role of KLK1 and KLK5 in influenza viral infection enhancement and its inhibition by Kallistatin was well established by Leu et al (2015) and Magnen et al (2017).…”
Section: Sars-cov-2: Human Proteases Involvement In Invasion and Immusupporting
confidence: 58%
“…Further, full inhibition was observed when the camostat mesylate was coupled with Cathepsin B/L inhibitor E-64d, indicating alternate protein priming by endosomal cysteine proteases Cathepsin B/L (Hoffmann et al, 2020). These results were in concert with another study where SPINT2 geneencoded protease inhibitor targeted TMPRSS2 and led to the restriction of cleavage-activation and viral growth for a range of influenza viruses (Straus et al, 2020). Furthermore, the role of KLK1 and KLK5 in influenza viral infection enhancement and its inhibition by Kallistatin was well established by Leu et al (2015) and Magnen et al (2017).…”
Section: Sars-cov-2: Human Proteases Involvement In Invasion and Immusupporting
confidence: 58%
“…Genes such as IFIT1 [ Feng et al, 2018 ], XAF1 [ Long et al, 2013 ], OAS3 [ Gad et al, 2012 ], CKB (creatine kinase B) [ Hara et al, 2009 ], RPL18A [ B. Wang et al, 2018 ], CIB1 [ Godinho-Santos et al, 2016 ] and EEF2 [ Valiente-Echeverría et al, 2014 ] were linked with advancement of various viral infections, but these genes may be liable for progression of SARS-CoV-2 infection. Genes such as OAS2 [ Zhao et al, 2019 ], CXCL10 [ Law et al, 2010 ] and SPINT2 [ Straus et al, 2020 ] were linked with progression of influenza virus infection, but these genes may be associated with development of SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Kinetic analysis has been reported so far for hepsin inhibition by the first Kunitz domain of HAI-1 ( 54 ) as well as for the matriptase-HAI-1 pair ( 55 , 56 ). In addition, HAI-1 and/or HAI-2 have been identified as physiologically relevant inhibitors of hepsin ( 50 ), TMPRSS2 ( 57 , 58 , 59 ), TMPRSS3 ( 57 ), TMPRSS4 ( 57 , 60 ), matriptase-2 ( 61 , 62 ), HATL1/TMPRSS11A ( 57 ), HAT/TMPRSS11D ( 63 ), DESC1/TMPRSS11E ( 64 ), TMPRSS13 ( 53 , 57 , 65 ), matriptase ( 58 , 60 , 66 , 67 , 68 , 69 , 70 ), enteropeptidase/TMPRSS15 ( 57 ), and prostasin ( 68 , 71 , 72 , 73 ). In fact, HAI-2 has been recently proposed as a broad-spectrum antiviral agent ( 58 ).…”
Section: Several Membrane-associated Serine Proteinases Might Synergimentioning
confidence: 99%
“…Thus, HAI-1 and HAI-2, as master regulators of all MASPs, would play an important role in SARS-CoV-2 propagation by regulating the availability of serine proteinase active sites on host cell membranes. Indeed, it has been recently shown that HAI-2 reduces cleavage/activation and growth of several influenza viruses by inhibiting TMPRSS2 or matriptase ( 58 ).…”
Section: Several Membrane-associated Serine Proteinases Might Synergimentioning
confidence: 99%